2020
DOI: 10.1002/chem.202001402
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine‐18 Radiolabelling and Photophysical Characteristics of Multimodal PET–Fluorescence Molecular Probes

Abstract: Positron emission tomography (PET)–fluorescence imaging is an emerging field of multimodality imaging seeking to attain synergy between the two techniques. The probes employed in PET–fluorescence imaging incorporate both a fluorophore and radioisotope which enable complementary information to be obtained from both imaging techniques via the administration of a single agent. Fluorine‐18 is the most commonly used radioisotope in PET imaging and consequently many novel attempts to radiofluorinate various fluoroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 126 publications
(185 reference statements)
0
16
0
Order By: Relevance
“…Optical imaging, owning the characteristics of excellent spatial resolution and sensitivity, has been applied to direct the resection of lesions in clinical surgery. 22,23 However, its application also be limited due to the poor tissue penetration. 24 Due to higher sensitivity, deeper tissue penetration and can provide more quantiable information, PET imaging may be superior to other imaging technologies in monitoring the expression level of GGT in living subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical imaging, owning the characteristics of excellent spatial resolution and sensitivity, has been applied to direct the resection of lesions in clinical surgery. 22,23 However, its application also be limited due to the poor tissue penetration. 24 Due to higher sensitivity, deeper tissue penetration and can provide more quantiable information, PET imaging may be superior to other imaging technologies in monitoring the expression level of GGT in living subject.…”
Section: Introductionmentioning
confidence: 99%
“…24 Due to higher sensitivity, deeper tissue penetration and can provide more quantiable information, PET imaging may be superior to other imaging technologies in monitoring the expression level of GGT in living subject. 22,[24][25][26] At present, GGT-targeting probes under preclinical study are mainly optical probes, while PET probes are rarely reported for detecting the GGT expression. 27 Recently, our group reported a GGT-targeting PET probe 18 F-1G to monitor the expression level of GGT in living subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The radiolabeled fluorophores as dual imaging probes combine the advantages of both modalities. Whereas nuclear imaging methods comprise (semi)quantitative non-invasive three-dimensional whole body imaging with high sensitivity and high tissue penetration, the low spatial resolution in the millimeter range can be balanced out by optical imaging methods [51,53,54]. Vice versa, the low tissue penetration of optical imaging methods can be compensated by using nuclear imaging techniques through high penetration properties.…”
Section: Introductionmentioning
confidence: 99%
“…This ideal cutting-edge concept leads to synergistic effects with high tissue penetration and spatial resolution overviewing the whole body and the subcellular compartments. In the literature, multiple PET and SPECT radionuclides were attached to small molecular fluorophores to perform multimodal imaging [51,53,55].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic approaches are discussed for each type of organic fluorescent dye followed by their applications in preclinical imaging. A recent review by Klenner et al also discusses multimodality imaging with 18 F [49]. The current work differs in its greater focus on alternative fluorophores, small molecules, and demonstrated applications in molecular imaging.…”
Section: Introductionmentioning
confidence: 99%